Sectoral Analysis in the Economic Development of Bogor Raya in West Java for the 2019-2023 Period - Rangga Febrian; Suryo Bintoro, Nugroho (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Regional development must be oriented toward sectoral advantages to optimize resource allocation and development strategies. Bogor Raya, which consists of Bogor City and Bogor Regency, based on the 2023 GRDP contribution rankings in West Java Province, shows that Bogor City ranks fourth out of nine cities, while Bogor Regency ranks third out of nineteen regencies. One of the largest sectors in Bogor Raya, namely Wholesale and Retail Trade, contributes less than the provincial level, indicating that this sector is more prominent at the provincial level. This study aims to analyze the regional economic sectors to determine development priorities for Bogor Raya. The analytical methods used include Location Quotient (LQ), Shift-Share (SS), Growth Ratio Model (GRM), and Overlay. The results show that eight sectors consistently remain either basic or non-basic, with only one sector changing category. One sector shifted from basic to non-basic, while six sectors shifted from non-basic to basic. Lastly, there are four leading sectors in Bogor Raya. This condition is influenced by the strategic role of Bogor Raya as the hinterland of the Jakarta region.